Legacies of agriculture and urbanization in labile and stable organic carbon and nitrogen in Sonoran Desert soils. Issue 5 (22nd May 2014) - Lewis, David Bruce; Kaye, Jason P.; Kinzig, Ann P.
Abstract : Soils regulate air and water quality by storing large pools of carbon (C) and nitrogen (N). Land management decisions have an enduring influence on the integrity and size of these pools, particularly in the upper soil layers. An important challenge, therefore, is to identify how soil C and N bear the marks of both past and present land use. Several studies have documented that effects of agriculture on soil properties can persist long after agricultural abandonment, but these studies typically examine sites returning to forest or grassland. Fewer have investigated legacies of agricultural land use when formerly agrarian land becomes urban. Urban soil management may be intensive, characterized by modifications in microtopography, vegetation, and nutrient and water inputs. We thus hypothesized that urban residential land use would negate any agrarian signatures in the pool sizes of labile (readily mineralized) soil organic C and N, but that agrarian legacies would persist in pools of stable (not readily mineralized) C and N. We tested this hypothesis in arid central Arizona (USA), where residential development in the Phoenix metropolis occurred on both agrarian and uncultivated desert lands throughout the 20th Century. We used a year‐long incubation to quantify labile and stable organic C and N in soils (to 15.2 cm depth) from desert land, contemporary agrarian land, residential yards that were converted from desert, and yards converted from agrarian land use. Labile N in residential soils may have been independent of historical provenance, consistent with the hypothesis that readily‐mineralized pools converge on a single signature of current (residential) land use. Labile C, stable C, and stable N showed the influence of agrarian history decades after conversion to urban residential use. These agrarian legacies in currently residential soil result from the persistence of past agrarian amendments to soil, and are not artifacts of the preferential cultivation of inherently fertile land. Current residential soil management is further amending soil C and N pools on top of the legacy pools left behind by agriculture. We calculate that the persisting influence of agrarian history on soils is similar in magnitude to contemporary urban residential effects.